Phylogenetics, ancestral state reconstruction, and a new infrageneric classification of Scleria (Cyperaceae) based on three DNA markers. Issue 3 (1st June 2016) - Bauters, Kenneth; Asselman, Pieter; Simpson, David A.; Muasya, A. Muthama; Goetghebeur, Paul; Larridon, Isabel
Abstract: The genus Scleria (Cyperaceae), with ca. 250 species, is placed in the monotypic tribe Sclerieae. It has a primarily pantropical distribution. Previously, infrageneric classifications have been proposed but none has been based on molecular phylogenetic evidence and most studies have treated the genus from only one geographical region. In this study, DNA portions from 101 species of Scleria from across its distributional range and all infrageneric groups were extracted and amplified for three molecular markers: the coding chloroplast marker ndhF, the chloroplast intron rps16 and the nuclear ribosomal region ITS. Phylogenetic hypotheses were constructed using Bayesian inference and maximum likelihood approaches. Additionally, ancestral states of four morphological characters were reconstructed at important nodes using the program BayesTraits. A new infrageneric classification based on molecular evidence and supported by morphology is presented. Scleria is confirmed as monophyletic and sister to tribe Bisboeckelereae. A subdivision of Scleria into four subgenera (S. subg. Browniae, S. subg. Hypoporum, S . subg. Scleria, S . subg. Trachylomia ) is supported by our results. In this paper, twelve major clades are recovered within Scleria subg. Scleria . Clear morphological diagnostic features match these clades. Ancestral state reconstruction indicates that androgynous spikelets, a zoniform hypogynium, a paniculate inflorescence with staminate and subandrogynous spikelets, and normal linear leaves are ancestral in Scleria . Androgynous spikelets are found in the three first‐branching subgenera, while in S . subg. Scleria an evolutionary shift towards subandrogynous and strictly unisexual spikelets is noted. Hypogynia are generally well developed with the exception of S . subg. Hypoporum, where the hypogynium is reduced or even lost. Inflorescences in Scleria vary from short, densely paniculate and pyramidal to subcapitate, only in S . subg. Hypoporum a glomerate‐spicate inflorescence is found. The pseudopremorse leaf habit arose only once within S . subg. Scleria . Scleria sect. Scleria shows a reversal to normal leaf tips.